Rate forward guidance in an environment of large central bank balance sheets: A Eurosystem stock-taking assessment (European Central Bank (ECB), 2022)
In the aftermath of the global financial crisis, central banks started being confronted with severe challenges that led to an unprecedented policy response in terms of the size and variety of monetary policy measures. One such measure centred on central banks communicating to the public more explicitly their future policy actions in order to influence expectations. In the case of interest rates, as the standard policy rate approached the effective lower bound, major central banks began providing forward guidance (FG) on interest rates with the intention of lowering expectations of future short-term rates. While FG had been used in certain jurisdictions before the crisis, its prominence in the monetary policy toolkit grew substantially in the aftermath of the crisis. This occasional paper summarises the work carried-out by the Eurosystem Taskforce on the macroeconomic impact of rate forward guidance (FG) in an environment of large central bank balance sheets. The analysis presented covers the period up to February 2020 so the implications of the pandemic as well as the ECB's strategy review are beyond the scope of the Taskforce's mandate. The paper describes the analytical challenges associated with assessing rate FG on account of the relative novelty of these policies, the lack of well-established empirical results and the sensitivity of model predictions to the expectations formation process. To overcome and address these challenges, the Taskforce took stock of all the available infrastructure and analysis within in the Eurosystem, and where needed, developed structural and empirical models and approaches to assess the macroeconomic impact of rate FG in an environment of large central bank balance sheets.
Keywords: E37; E43; E52; E58; 330; ECB policy; effective lower bound; monetary policy; forward guidance